Індикатори управління безпекою харчування дітей - Коноваленко, Анастасія Сергіївна; Коноваленко, Анастасия Сергеевна; Konovalenko, Anastasiia (My University, 2021)
UK: Забезпечення безпеки харчування дітей є стратегічним завданням держави та потребує наукового обґрунтування шляхів, напрямів використання існуючого потенціалу його підвищення. У статті запропоновано алгоритм моніторингу ефективності управління, що передбачає послідовні етапи з урахуванням впровадження маркетингового механізму. Розробка стратегічних напрямів підвищення безпеки харчування дітей потребує моніторингу поточного стану, визначення чинників існуючої динаміки, що ускладнено відсутністю методичних підходів до оцінки ефективності управління безпекою харчування. На основі аналізу компонентів продовольчої безпеки зазначено параметри безпеки харчування дітей, засновані на критеріях Римської декларації про всесвітню продовольчу безпеку та FAO. Запропоновано систему ключових індикаторів рівня безпеки харчування дітей, які передбачають макроекономічні та маркетингові індикатори, що характеризують рівень фізичної та фінансової доступності продовольства, якості та безпечності продуктів харчування, а також враховують поведінковий аспект. Окреслено методи збору інформації для оцінки управління безпекою харчування дітей, що передбачають отримання як вторинної, так і первинної інформації. RU: Обеспечение безопасности питания детей является стратегической задачей государства и требует научного обоснования путей, направлений использования существующего потенциала его повышения. В статье предложен алгоритм мониторинга эффективности управления, который предполагает последовательные этапы с учетом внедрения маркетингового механизма. Разработка стратегических направлений повышения безопасности питания детей требует мониторинга текущего состояния, определения факторов существующей динамики, что затруднено отсутствием методических подходов к оценке эффективности управления безопасностью питания детей. На основе анализа компонентов продовольственной безопасности указано параметры безопасности питания детей, основанные на критериях Римской декларации о всемирной продовольственной безопасности и FAO. Предложена система ключевых индикаторов уровня безопасности питания детей, предусматривающих макроэкономические и маркетинговые индикаторы, характеризующие уровень физической и финансовой доступности продовольствия, качества и безопасности продуктов питания, а также учитывают поведенческий аспект. Определены методы сбора информации для оценки управления безопасностью питания детей, которые предполагают получение в качестве вторичной, так и первичной информации. EN: Ensuring the safety of children's nutrition is a strategic task of the state and requires a scientific justification of ways, directions of using the existing potential to increase it. The article considers approaches to assessing the effectiveness of nutrition management of school-age children, proposes an algorithm for monitoring the effectiveness of management, which provides for the cyclical implementation of a number of successive stages, taking into account the implementation of the marketing mechanism. It is noted that according to the overall rating of the Global Food Security Index, Ukraine in 2019 improved its position compared to the previous period, which characterizes the presence of positive changes in the field of food security. However, the adjustment of existing programs and the development of new strategic directions for improving the safety of children's nutrition requires monitoring of the current situation, determining the factors of the existing dynamics, which is complicated by the lack of methodological approaches to assessing the effectiveness of food safety management. Based on the analysis of the components of food security, the children' food safety parameters based on the criteria of the Rome Declaration on World Food Security and FAO are indicated. A system of key indicators for children's food safety is proposed, providing macroeconomic and marketing indicators that characterize the level of physical and financial availability of food, quality and safety of food, and take into account behavioral aspects (namely motivated choice of healthy food by children). The behavioral aspect of food safety is manifested through the model of children's consuming behavior in the market. Methods of collecting information for the assessment of child nutrition safety management, which provide for obtaining both secondary and primary information, are outlined.
Индикаторы управления безопасностью питания детей
Child nutrition safety management indicators
Keywords: безпека харчування; споживач; індикатори; продовольча безпека; поведінка споживача; безопасность питания; потребитель; индикаторы; продовольственная безопасность; поведение потребителя; food safety; consumer; indicators; food security; consumer behavior